Effects of temperature on eggs and larvae of Anisakis simplex sensu stricto and Anisakis pegreffii (Nematoda: Anisakidae) and its possible role on their geographic distributions. (February 2023) - Gomes, Tiago Leandro; Quiazon, Karl Marx; Itoh, Naoki; Fujise, Yoshihiro; Yoshinaga, Tomoyoshi
Abstract: Effects of temperature on development of eggs, recently hatched larvae and L3 larvae of the marine parasitic nematodes Anisakis simplex sensu stricto (s.s.) and A. pegreffii were examined in vitro . The eggs of A. simplex s.s. hatched at 3–25 °C and those of A. pegreffii hatched at 3–27 °C. Days before hatching varied between 2 days at 25 °C and 35–36 days at 3 °C in A. simplex s.s. and between 2 and 3 days at 27 °C and 65 days at 3 °C in A. pegreffii . Hatching rates of A. simplex s.s. were maintained high at temperatures between 3 and 25 °C but decreased to 0% at 27 °C. In contrast, those of A. pegreffii were lowest particularly at 3 °C, but also at 27 °C. The mean 50% survivals of hatched larvae ranged from 5.3 days at 25 °C to 82.3 days at 9 °C in A. simplex s.s., while in A. pegreffii it ranged from 1.2 days at 27 °C to 77.2 days at 9 °C. L3 larvae of A. pegreffii exhibited higher survival rates and activity than those of A. simplex s.s., particularly at 20 and 25 °C. These results suggest that the early stages of A. simplex s.s. are more adapted to lower temperatures whereas those of A. pegreffii are more tolerant to warm environments, which may correspond to their distribution patterns in Japan and Europe.